RASHAD KHALIFAH : INGKAR SUNNAH DAN PEMIKIRANNYA - Muti'a, Nadratun; Jamal, Khairunnas; Hakim, Lukmanul (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
This research discusses Rashad Khalifa's thoughts on the Qur'an and his rejection of the Sunnah. Rashad Khalifa considers the Qur'an to be perfect and believes that there is no need for Hadith and Sunnah. His rejection of the Sunnah is reinforced by his notable works, particularly the famous one known as the numerical miracle of the Qur'an, often referred to as code 19. The aim of this research is to understand Khalifa's rejection of the Sunnah and his thoughts. The method employed is a literature review (library research), involving the collection of data through the study and analysis of books, literature, and reports related to the problem at hand. The findings of this research reveal that Rashad Khalifa is a figure who rejects the Sunnah, firmly believing in the Qur'an as the sole source of Islamic law and denying the importance of the Sunnah. His formulations regarding the Sunnah contain numerous errors and misconceptions that lead to the rejection of Hadith (denial of the Sunnah) and the Anti-Hadith Movement (denial of the Sunnah).